Characterization of deepwater invertebrates at Isla del Coco National Park and Las Gemelas Seamount, Costa Rica - Starr, Richard M. (2012)
The deepwater faunas of oceanic islands and seamounts of the Eastern Tropical Pacific are poorly known. From 11-22 September 2009, we conducted an exploration of the deepwater areas around Isla del Coco National Park and Las Gemelas Seamount, located about 50km southwest of Isla del Coco, Costa Rica using a manned submersible to survey the seafloor habitats. The goal of the exploration was to characterize the habi-tats and biota, and conduct quantitative surveys of the deepwater portions of Isla del Coco National Park and Las Gemelas. We completed a total of 22 successful submersible dives, spanning more than 80hr underwater, and collected a total of 36hr of video. With respect to invertebrates, our objectives were to gather quantitative information on species composition, density, distribution and habitat associations as well as to compare the invertebrate communities between the two sites. A total of 7 172 invertebrates were counted from analysis of the video collected on this project. Larger organisms were counted and placed into 27 taxonomic groups to characterize the deepwater invertebrate fauna of Las Gemelas Seamount and Isla del Coco National Park. The Shannon-Weiner Index for biodiversity (H’) was calculated to be 0.14 ± 0.02 for Isla del Coco and 0.07 ± 0.03 for Las Gemelas surveys. Although richness was fairly equal between the two sites, evenness was greater at Isla del Coco (J = 0.04 ± 0.006) when compared to Las Gemelas (J = 0.02 ± 0.01). This lower level of evenness in the community at Las Gemelas was a result of high densities of a few dominant species groups, specifically sea urchins and black corals. We also evaluated invertebrate percent cover at both Isla del Coco and Las Gemelas Seamount with respect to habitat type, slope and rugosity. Results indicated that highly rugose habitats contained the highest frequencies of all invertebrates at both sites, with the exception of glass sponges and polychaetes at Isla del Coco, which were found in greater quantities at intermediate levels of rugosity. Information obtained from these submersible surveys indicate that seamounts in the tropical eastern Pacific Ocean may be an impor-tant source of biodiversity and that more quantitative surveys are needed to characterize the fauna of the region.